2018
DOI: 10.1016/j.ymthe.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Global MicroRNA Profiling in Human Bone Marrow Skeletal—Stromal or Mesenchymal–Stem Cells Identified Candidates for Bone Regeneration

Abstract: Bone remodeling and regeneration are highly regulated multistep processes involving posttranscriptional regulation by microRNAs (miRNAs). Here, we performed a global profiling of differentially expressed miRNAs in bone-marrow-derived skeletal cells (BMSCs; also known as stromal or mesenchymal stem cells) during in vitro osteoblast differentiation. We functionally validated the regulatory effects of several miRNAs on osteoblast differentiation and identified 15 miRNAs, most significantly miR-222 and miR-423, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…In our previous studies, we identified two miRNAs involved in bone regeneration: (i) miRNA-675-5p as a modulator of HIF-1α and Wnt/β-catenin signalings in human mesenchymal stromal cells (hMSCs) [6]; and (ii) miRNA-31-5p, a mechanosensitive miRNA involved in hMSCs hypoxia response [7]. Microarray analysis revealed that hMSCs and osteoblast cells showed strong differences in terms of miRNAs expression and relative signaling activation [8,9], such as epithelial-to-mesenchymal transition (EMT) pathway [9] and the epidermal growth factor (EGF) signaling [10], which are strongly correlated to hypoxia cell response during osteoblast differentiation [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we identified two miRNAs involved in bone regeneration: (i) miRNA-675-5p as a modulator of HIF-1α and Wnt/β-catenin signalings in human mesenchymal stromal cells (hMSCs) [6]; and (ii) miRNA-31-5p, a mechanosensitive miRNA involved in hMSCs hypoxia response [7]. Microarray analysis revealed that hMSCs and osteoblast cells showed strong differences in terms of miRNAs expression and relative signaling activation [8,9], such as epithelial-to-mesenchymal transition (EMT) pathway [9] and the epidermal growth factor (EGF) signaling [10], which are strongly correlated to hypoxia cell response during osteoblast differentiation [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we wanted to understand the role of the miR-33a family during hMSCs osteoblast commitment and their relative targets using hMSCs as a model of stromal cells, hMSCs maintained in osteogenic medium as a model of pre-osteoblast cells, and Nh-Ost as a model of osteoblast cells [8,9]. Starting from the recent evidence that displayed a different miRNAs expression profiling between hMSCs and Nh-Ost as well as from our previous studies in which we demonstrated the roles of miR-675-5p and miR-31-5p in hypoxia and cytoskeletal modulation during hMSCs osteoblast differentiation [6,7], we decided to investigate another important signaling involved in hMSCs osteoblast commitment, such as EMT, for which it has been demonstrated that miR-33a shows a different mRNAs interaction.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6 These markers are sensitive but not predictive of the differentiation capacity of the cells. 9,14 Several studies have identified a molecular signature for bone-forming hBM-MSCs by applying global analysis of gene expression, 9,15,16 miRNA expression, 17,18 or proteome analysis. 19,20 Although these approaches contribute significantly to understanding the biology and functions of hBM-MSCs, they are labor-intensive, use a large number of cells, and may not be easy to implement in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…We previously identified unrecognized differences in a potential gene regulatory network in mouse frontal bone and parietal bone . Recently, micro ribonucleic acids (miRNAs) have been reported to play regulatory roles in the skeletal homeostasis . MiRNA‐378 can fuel osteogenesis‐angiogenesis for bone regeneration, and miR‐335‐5p can down‐regulate DKK1to boost osteogenic differentiation, and the modification of miR‐335‐5p was sufficient to enhance calvarial bone regeneration and minimize bone defects .…”
Section: Introductionmentioning
confidence: 99%
“…6 Recently, micro ribonucleic acids (miRNAs) have been reported to play regulatory roles in the skeletal homeostasis. [13][14][15] MiRNA-378 can fuel osteogenesis-angiogenesis for bone regeneration, 16 and miR-335-5p can down-regulate DKK1to boost osteogenic differentiation, and the modification of miR-335-5p was sufficient to enhance calvarial bone regeneration and minimize bone defects. 17 Therefore, miRNAs can be potential therapeutic targets to treat the skeletal disorders, but the potential miRNAs in the frontal bone and parietal bone are still illusive.…”
Section: Introductionmentioning
confidence: 99%